P–229 Oxidative stress and Metformin; an in-vitro study on serum and primary human granulosa cell cultures. (6th August 2021) - Alam, F; Rehman, R; Farooqui, N; Jehan, F; Abidi, S H
Abstract: Study question: What is the effect of administration of Metformin on the oxidative stress (OS) levels in serum and primary human granulosa cell cultures of infertile females? Summary answer: Metformin suppresses oxidative stress in serum and human granulosa cells and increases the expression of SIRT1 in OS induced environment. What is known already: Oxidative stress (OS) is a resultant of mitochondrial dysfunction when it either fails to fight against the oxidants or the expression of the antioxidants is not sufficient. Cellular damage including DNA damage is a common resultant of oxidative stress. OS effects the oocyte maturation and moreover, the cleavage phase in the early embryonic stage. The raised levels of OS makers are hypothesized to compromise the nuclear maturation and the mitotic spindles of the maturing oocytes. Metformin seemed to decrease oxidative stress and improve insulin resistance, dyslipidaemia and endothelial dysfunction in PCOS patients Study design, size, duration: This cross-sectional study was conducted from August 2017 – July 2019, at Aga Khan Hospital in collaboration with Australian Concept Infertility Medical Centre (ACIMC) on ten infertile patients undergoing egg retrieval after ethical approval from of Aga Khan Hospital (AKU-ERC–2018–0557–601). Participants/materials, setting, methods: Serum samples were obtained and analysed. Follicular fluid of these subjects was collected for establishment of primary cell culture model of normal human granulosa cells (hGCs). Serum and hGC cultures were grouped as; a) control: treatment, b) Test1: H2O2 induced OS, and c) Test2: H2O2 induced OS treated with metformin. OS was estimated in all groups by Mishra method. The two Test groups were assessed for SIRT1 levels using quantitative PCR employing SIRT1 specific primers Main results and the role of chance: With mean age of 32.04 ± 2.29 years the mean BMI was 27.61 ± 2.15 kg/m2. OS was induced and measured by an increase in optical density (OD) in hGC Test samples which showed 0.28 (0.16–0.40) OD when compared with control hGC samples 0.153 (0.09–0.23). There was a significant reduction in ODs after metformin treatment in the stress induced cells 0.182 (0.05–0.30). A similar pattern was observed in the serum samples in ODs; control: 0.105 (0.09–0.15), stress induced samples: 0.199 (0.19–0.20). and stress induced serum sample with metformin treatment: 0.1415 (0.06–0.18). The Ct values obtained to express the effect of metformin on SIRT1 levels, for OS induced (Test1) and OS induced metformin treated (Test2) cells were found to be 29.12 and 26.42, respectively. We also observed a significant (85%) difference in the fold change of SIRT1 expression between metformin treated and untreated cells. Limitations, reasons for caution: Small sample size is the limitation of this study. The impact of metformin on cell cultures due to different causes of infertility could not be ascertained Wider implications of the findings: Metformin suppresses oxidative stress in serum and human granulosa cells and increases the expression of SIRT1 in OS induced environment, therefore, metformin may be considered as a treatment of oxidative stress in infertile patients. Randomized control trial with large sample size is recommended to confirm the cause and effect relationship. Trial registration number: Not applicable